2019
DOI: 10.1155/2019/3137927
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Complex Quadrature Spatial Modulation

Abstract: Spatial modulation (SM) is a multiple-input multiple-output (MIMO) system that achieves a MIMO high spectral efficiency while maintaining the transmitter computational complexity and requirements as low as those of the single-input systems. The complex quadrature spatial modulation (CQSM) builds on the QSM scheme and improves the spectral efficiency by transmitting two signal symbols at each channel use. In this paper, we propose two generalizations of CQSM, namely, generalized CQSM with unique combinations (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…The receiver; due to a fact that one (or a set of) transmit antenna (s) are active in one transmit period, will try to detect the received bits. The complexity of achieving this detection (or prediction) depeds on many factors related to the detection method itself, channel behavior, constellation order, channel estimation accuracy, and number of bits conveyed in selecting transmit antennas (as the number of spatial bits increase, complexity increases [23,24]).…”
Section: Miso-ofdm-sm System Modelmentioning
confidence: 99%
“…The receiver; due to a fact that one (or a set of) transmit antenna (s) are active in one transmit period, will try to detect the received bits. The complexity of achieving this detection (or prediction) depeds on many factors related to the detection method itself, channel behavior, constellation order, channel estimation accuracy, and number of bits conveyed in selecting transmit antennas (as the number of spatial bits increase, complexity increases [23,24]).…”
Section: Miso-ofdm-sm System Modelmentioning
confidence: 99%
“…It improves the SE by transmitting two amplitude/phase modulated symbols drawn from two different constellation sets at each channel use, using unique combinations of generalized I domain antennas and Q domain antennas. The two symbols could be transmitted from the same antenna at one point, and thus the total modulation set at the transmitter becomes the Minkowski sum of the original two constellation sets 12 . Therefore, compared to C-SM and C-QSM, this leads to an increase in the size of the modulation set and a decrease in the minimum distance between transmitted symbols at the transmitter of GCQSM systems, which in turn results in the degradation of the EP of the GCQSM scheme 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Cogen et al 17 , also solved the error floor degradation of the EP of QSM systems by rotating the H-QAM symbols. Also, in 12 , Mohaisen et al investigated the rotation of symbols in GCQSM systems which also led to an improvement in the EP of GCQSM systems. In Naidoo et al 14 , and Singya et al 15 , the EP of SM systems was also found to depend on the M-MED between two neighbouring constellation points and the average symbol energy.…”
Section: Introductionmentioning
confidence: 99%
“…The constellation design of this system is investigated in Reference [ 25 ]. Another approach used to avoid the symbols’ overlapping and to reduce the number of transmit antennas by using antenna combinations is proposed in Reference [ 26 ]. Improved QSM (IQSM) exploits the in-phase and quadrature spatial dimensions to transmit the real and imaginary parts of two signal symbols, respectively, using combinations of two antennas [ 27 ].…”
Section: Introductionmentioning
confidence: 99%